The Impact of Corruption on Access to Health Services for the Poor (A Case Study of Health Operational Assistance (BOK) Funds in Central Aceh) - Afini; Muhammad Arif Sahlepi; Marice Simarmata (Judge : Jurnal Hukum, 2026)
This study aims to analyze the impact of corruption in Health Operational Assistance (BOK) funds on the accessibility of health services for the poor in Central Aceh Regency during the 2022-2023 period, as well as to review the effectiveness of governance improvements following the investigation. The research employs a socio-legal (empirical) method with a qualitative approach. Primary data were collected through in-depth interviews with 30 health workers and 40 poor community respondents in the working areas of Bebesen and Pegasing Puskesmas, along with field observations and an analysis of Aceh Regional Police (Polda Aceh) investigation documents.The results reveal that the alleged corruption of BOK funds for the 2022-2023 fiscal year, amounting to IDR 5.3 billion, stemmed from the abuse of authority through fictitious reporting and budget markups across 45 activities. Empirically, this practice resulted in a degradation of outreach service quality (Posyandu and Pusling) and illegal deductions from health workers' honorariums. However, field findings in 2026 indicate a significant positive transformation following the enactment of Minister of Health Regulation Number 18 of 2024, where the direct funding mechanism to Puskesmas accounts successfully minimized bureaucratic intervention at the Health Office level. Furthermore, the limited budget ceiling often does not match the actual needs in the field. This study concludes that firm law enforcement based on Article 4 of the Anti-Corruption Law must be coupled with the provision of free medical transportation services to ensure the full constitutional rights of the poor to health.